Brazilian Portuguese version of the Iowa Gambling Task: transcultural adaptation and discriminant validity - Malloy-Diniz,Leandro Fernandes (2008)
OBJECTIVE: The Iowa Gambling Task is a neuropsychological task developed in English, most widely used to assess decision-making. The aim of this work was to adapt the Iowa Gambling Task to Brazilian Portuguese, compare it with the original version and assess its validity. METHOD: We assessed 75 Brazilian adults divided into three groups: 1) 25 healthy volunteers holding the Proficiency Certificate in English tested using the English version of the Iowa Gambling Task; 2) 25 healthy volunteers who did not speak or read English tested using the Iowa Gambling Task-Portuguese; 3) 25 Attention Deficit Hyperactivity Disorder subjects tested with the Iowa Gambling Task-Portuguese. RESULTS: No difference between groups 1 and 2 was observed. Nonetheless, we found significant differences between Attention Deficit Hyperactivity Disorder subjects and the other 2 groups on blocks 3, 4, 5, and on net score. CONCLUSION: Our results are similar to those previously described in the literature concerning adults without neuropsychiatric diseases. Since those two versions were equivalent and Attention Deficit Hyperactivity Disorder subjects performed significantly worse than healthy volunteers we can conclude that the adaptation of the Iowa Gambling Task to Brazilian Portuguese is valid and can be used for research purposes in the Brazilian context.